A COMPREHENSIVE MECHANISM OF PUBLIC ADMINISTRATION TO ENSURE THE FORMATION OF ORGANIZATIONAL AND STAFF STRUCTURES OF BORDER UNITS - Kirylenko , V.; Mejko , O. (Pressing Problems of Public Administration, 2020)
The article analyses the problem of functioning of the mechanism of state administration of the organizational and staff structure of the border unit. The results of the analysis of the scientific literature on the proposed problem are presented. The purpose of the scientific publication is formulated. An overview of the Strategy of the Ministry of Internal Affairs of Ukraine and the State Border Service in particular is presented in the main material. The definition of the mechanism of public administration in the border area of activity (MISPS) is a mechanism as a system intended for practical implementation of state policy in the field of state border protection and achievement of set goals, which (system) has a defined structure and tools (methods, methods, legal and regulatory levers, resource [including information and analytical] support for the control object. The structure of a complex mechanism, which includes several interdependent mechanisms, is revealed: the organizational mechanism of public administration by providing the formation of organizational and staff structures of border units; the legal mechanism of public administration to ensure the formation of organizational and staff structures of border units; a resource mechanism of public administration to ensure the formation of organizational and staff structures of border units. The content of each resource in the complex mechanisms of state management of the organizational and staff structure of the border unit is analysed. The organizational mechanism is one of the most effective at all levels (tactical, operational-tactical, operational-strategic and strategic) of the military control system. The legal mechanism provides for: development and improvement of the legal framework with the neighbouring countries on the common state border with the utmost consideration of the national interests of Ukraine; legislative support for the processes of contractual legal registration of the state border of Ukraine; improvement and optimization of the current legislation on the formation and development of the security and defence sector of Ukraine, creation. It is noted that the qualitative implementation of a comprehensive mechanism of public administration by ensuring the formation of organizational and staff structure of border units is possible only under the conditions of qualitative organization of information and analytical activities.